INFLUENZA VACCINATION OF CHILDREN OF PRESCHOOL AGE IN THE RUSSIAN FEDERATION: COST-EFFECTIVENESS OF QUADRIVALENT VACCINE - A. V. Rudakova; D. M. Danilenko; D. A. Lioznov; L. S. Karpova; S. M. Kharit; E. V. Mikitenko; A. N. Uskov; A. S. Kolbin; L. N. Konovalova; Yu. V. Lobzin (Журнал инфектологии, 2019)
According to requirements of WHO, the trivalent influenza vaccines (TIV) have to contain antigens of two influenza A strains (A/H1N1, A/H3N2) and one influenza B strain which can be presented by antigens of a virus of lineages Yamagata or Victoria. In a season of 2017/2018 the discrepancy of the vaccinal and circulating influenza B strains was noted that caused decrease in effectiveness of vaccination, especially at children’s age when the frequency of detection of influenza B is higher, than in other age groups. Now in the Russian Federation it is registered, in addition to TIV, quadrivalent vaccine (QIV) manufactured in the Russian Federation and including antigens of influenza B viruses of the two lineages.The purpose of work was assessment of the cost-effectiveness of QIV in comparison with TIV at children of preschool age on the basis of epidemiological data on the Russian Federation for a season of 2017/2018.Material and methods. The analysis was carried out by a modeling method from a health care system and societal perspective taking into account epidemiological data on the Russian Federation and the European data on effectiveness of TIV at citizens of various age. Indirect effect of vaccination was not considered. The cost of the TIV and QIV (Grippol plus and Grippol quadrivalent, respectively) corresponded to the registered price including VAT.Results. The analysis showed that use QIV instead of TIV for children of preschool age in an epidemiological season of 2017/2018 would allow to increase quantity of the prevented influenza cases by 17.1%. The prevented indirect costs exceed the prevented direct medical costs. The incremental cost-effectiveness ratio (ICER) is 1042.65-1093.7 thousand rubles/QALY in the analysis from the health care system perspective and 124.50-267.91 thousand rubles/QALY in the analysis from the societal perspective.Conclusions. Vaccination against influenza of children of preschool age in the Russian Federation in a season of 2017/2018 with quadrivalent vaccine would allow to increase significantly the number of the prevented cases of disease and could be considered as economically highly effective intervention. Reduction of vaccine price less, than for 5% in comparison with the registered price would allow to avoid completely additional budget burden.